New cases of pathogens imported with ornamental fish - Sobecka, Ewa; Łuczak, Ewa; Marcinkiewicz, Michał (Biological Letters, 2013)
The global trade in live ornamental fish carries with it the potential threat of unwanted movement of pathogens. The live ornamental fish, when released into the natural environment of their destination countries, may disseminate their parasites, threatening local fish and causing economic loss in fish aquaculture. This study was aimed to explain the reasons for deterioration of health and premature death of ornamental fish: Nannostomus spp. from Colombia and Symphysodon spp. Some specimens of Symphysodon aequifasciatus Pellegrin, 1904 were captured from their natural habitats in the Amazon River basin and shipped to Poland by air mail. The hybrids of Symphysodon spp. originated from an aquarium in Poland (shared with S. aequifasciatus). The third discus fish species, Symphysodon discus Heckel, 1840 came from a fish farm in Thailand and represents an Asian breeding line. All the studied fish were infected with pathogens. Nannostomus spp. housed a single parasite species on its skin, namely Artystone minima. This isopod species was not recorded in Poland and probably in Europe before. The examined fish of the genus Symphysodon yielded 13 pathogens. Five of them Philodina sp., Ichthyobodo necator, Hexamita symphysodonis, Sciadicleithrum variabilum and Eustrongylides sp. were not earlier recorded in this host species in Poland. The findings of Ichthyophonus hoferi and Myxobolus sp. are new host records for Symphysodon spp. fish. Hybrid fish and S. aequifasciatus are reported here as hosts of Entamoeba sp. for the first time.